The Effectiveness of the E-Library as a Learning Resource for Elementary School Students' Social Studies in Improving Literacy Skills - Marsini Marsini (AL-ISHLAH: Jurnal Pendidikan, 2023)
The aim of this study is to describe the effectiveness of an e-library as a social study (hereafter, IPS) learning resource for elementary school students in improving their literacy skills. When developing learning materials for social studies, Social Studies (IPS) teachers in elementary schools should have a clear goal and direction, including the use of e-library resources that can enhance students' literacy skills. A descriptive qualitative research approach was utilised to examine the efficacy of the e-library as a learning resource for primary school pupils in the field of social sciences, with a specific focus on enhancing their reading abilities. Data was collected through a literature review and document analysis on social studies learning in elementary schools, literacy skills, and e-libraries. In this investigation, up to  40 research articles were used. The findings indicated that the e-library was effective in helping primary school students study social subjects and develop their literacy skills. In order to optimize the potential of the library, the government or schools should: 1) provide relevant learning resources; 2) establish a 24-hour accessible system; 3) employ a creative librarian; and 4) utilize information technology to target students. This will enable students to access and acquire learning content easily. Additionally, the library should create a space for students to express their ideas freely and channel creativity, making library activities more lively and enjoyable.